Removal of estrogen pollutants using biochar-pellet-supported nanoscale zero-valent iron. (24th May 2022) - Deng, Peiyuan; Wang, Guangzhou; Li, Changkan; Dou, Shentang; Yuan, Wei
Abstract: Nanoscale zero-valent iron-supported biochar pellets (nZVI)-(BP) were synthesized via liquid-phase reduction and applied to estrogen removal, including estrone (E1), 17 β -estradiol (E2), and estriol (E3). The performance of nZVI-BP, with respect to its characterization, removal kinetics, and isotherms, was investigated. The results showed that the adsorption equilibrium was reached within 10 min of exposure. The adsorption capacity of estrogen decreased with increasing solute pH and nZVI-BP dosage. The adsorptivity increased with increasing initial estrogen concentration. The estrogen behavior followed a pseudo-second-order kinetic model. The adsorption data of different initial estrogen concentrations fitted to Freundlich adsorption isotherms. In addition, a preliminary discussion of the adsorption mechanism of nZVI-BP for estrogens was provided. HIGHLIGHTS: BP-supported nZVI was prepared to apply for removing estrogens. The proper reaction conditions were recommended for estrogen removal. The mechanisms of estrogen removal by BP-supported nZVI were probed. Graphical Abstract